2018
DOI: 10.1002/jcp.27033
|View full text |Cite
|
Sign up to set email alerts
|

NKCC1 promotes EMT‐like process in GBM via RhoA and Rac1 signaling pathways

Abstract: Glioblastoma is the most common and lethal primary intracranial tumor. As the key regulator of tumor cell volume, sodium‐potassium‐chloride cotransporter 1 (NKCC1) expression increases along with the malignancy of the glioma, and NKCC1 has been implicated in glioblastoma invasion. However, little is known about the role of NKCC1 in the epithelial‐mesenchymal transition‐like process in gliomas. We noticed that aberrantly elevated expression of NKCC1 leads to changes in the shape, polarity, and adhesion of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Protein targets of particular interest to us include Roundabout homolog 1 (Robol), a protein identified as key to normal and cancer cell migration; [16][17][18] yes-associated protein 1 (YAP1), which promotes growth of GBM cells; [19,20] sodium-potassium-chloride cotransporter (NKCC1), an ion transporter that affects cancer cell migration; [21,22] survivin, an anti-apoptotic gene whose expression in GBM correlates with proliferation [23] and with poor prognosis; [24] and endothelial growth factor receptor (EGFR), an oncogene whose aberrant expression is among the most common mutations in GBM. [25][26][27] Other reports of knockdown of Robo1, [18] YAP1, [28] NKCC1, [21,29] survivin, [30] or EGFR [31] often focus on knockdown of a single gene to isolate cellular mechanisms of GBM survival, growth, and invasion. Of the studies that have used RNAi against one of these targets as a therapeutic strategy, to our knowledge, this is the first report of a delivery system that causes knockdown of all five of these targets at once for GBM therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Protein targets of particular interest to us include Roundabout homolog 1 (Robol), a protein identified as key to normal and cancer cell migration; [16][17][18] yes-associated protein 1 (YAP1), which promotes growth of GBM cells; [19,20] sodium-potassium-chloride cotransporter (NKCC1), an ion transporter that affects cancer cell migration; [21,22] survivin, an anti-apoptotic gene whose expression in GBM correlates with proliferation [23] and with poor prognosis; [24] and endothelial growth factor receptor (EGFR), an oncogene whose aberrant expression is among the most common mutations in GBM. [25][26][27] Other reports of knockdown of Robo1, [18] YAP1, [28] NKCC1, [21,29] survivin, [30] or EGFR [31] often focus on knockdown of a single gene to isolate cellular mechanisms of GBM survival, growth, and invasion. Of the studies that have used RNAi against one of these targets as a therapeutic strategy, to our knowledge, this is the first report of a delivery system that causes knockdown of all five of these targets at once for GBM therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we found that IR could induce the up-regulation of RAC1 expression and activity via activating the PI3K/AKT signaling pathway (36,(48)(49)(50). Interestingly, IRinduced EMT is regulated by RAC1, a member of the Rho family of small guanosine triphosphatases (GTPases) that has been shown to play a critical role in cytoskeleton reorganization, cell migration and cell survival (51,52). Thus, we raised the possibility that RAC1 might be an important regulator in the process of IR-induced EMT in lung cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The exchanger works in close association with CAII. Some authors consider NKCC1 expression as a potential pro-tumoral agent [105][106][107][108]. NKCC1 indirectly participates in cytoplasmic alkalinization through its association with the Cl − /CO 3 H − exchanger [109].…”
Section: The Phtome and How The Paradigm Appearsmentioning
confidence: 99%